Evaluating the user experience of a Muslimah fashion e-commerce website using heuristic evaluation method - Mohamed Noor, Afiqah Zawani; Megat Zainuddin, Norziha; Ibrahim, Roslina; Yahya, Yazriwati; Sheikh Abdul Aziz, Madihah (2020)
As the buying and selling of Muslimah fashion products online become increasingly popular, the players in this E-commerce industry need to aim to make the online shopping experience even more seamless. Despite that, there is still a lack of understanding concerning the importance of user experience and its potential impact on the user satisfaction, conversion rates and ongoing revenues. The preliminary study’s result has confirmed that customer facing bad user experience while browsing E-commerce muslimah fashion site. This majorly due to the bad design interface, hardly understood information about the product as well as receiving lack of service from the E-commerce Muslimah fashion site in Malaysia. An instrument was proposed to evaluate the E-commerce Muslimah fashion site in Malaysia and the Ten General Principle in Interaction Design by Nielsen's has been used as the foundation in developing the propose instrument. The instrument was validated based on the comments and suggestions from the Face validation and Content Validity Index (CVI). A Heuristic Evaluation was used as the inspection method to evaluate the user experience of E-commerce Muslimah fashion site in Malaysia with three experts and Usability Percentage has been used to evaluate the result. Findings of the value for the Content Validity Index is 0.91. Meanwhile, the mean of the Usability Percentage values is 83.31%. The findings show that the propose instrument is a valid inspection method for evaluating the user experience of Muslimah Fashion E-commerce website in Malaysia.